2018
DOI: 10.1002/elps.201800455
|View full text |Cite
|
Sign up to set email alerts
|

Separation and simultaneous determination of seven bioactive components in Tripterygium wilfordii Hook. F. and Tripterygium preparations by micellar electrokinetic capillary chromatography

Abstract: A simple, comprehensive, and highly selective MEKC method has been developed for simultaneous analysis of seven bioactive components (triptolide, wilfortrine, wilfordine, wilforgine, wilforine, triptophenolide, and triptonide) in the root extracts of Tripterygium wilfordii Hook. F. (TWHF) and Tripterygium preparations (TPs). Optimal BGE consisted of 10 mM sodium tetraborate, 30 mM SDS, and 30% v/v methanol. The separation voltage was 20 kV and the temperature was 25°C. A DAD was used and the detection waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Further, the complex structure of the pentacyclic triterpenoid celastrol highlights the complexity of plant extracts. After induction of CMCs of T. wilfordii in our work, UPLC results showed that the production of triptolide, celastrol and triptophenolide in CMCs was 53, 10 and 4.62 times higher than those of the T. wilfordii plant which has been reported previously, respectively [38, 39].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Further, the complex structure of the pentacyclic triterpenoid celastrol highlights the complexity of plant extracts. After induction of CMCs of T. wilfordii in our work, UPLC results showed that the production of triptolide, celastrol and triptophenolide in CMCs was 53, 10 and 4.62 times higher than those of the T. wilfordii plant which has been reported previously, respectively [38, 39].…”
Section: Discussionsupporting
confidence: 81%
“…Most bioactive terpenoids are present in low amounts in the T. wilfordii plant with the mean concentrations of 7.61, 53.83 and 179 μg g −1 for triptolide, celastrol and triptophenolide, respectively [38, 39]. Further, the complex structure of the pentacyclic triterpenoid celastrol highlights the complexity of plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In MEKC, the surfactants are used as additives in the running buffer and the concentration higher than the critical micelle concentration (CMC) to provide a micellar pseudo‐stationary phase. The analytes are distributed between the aqueous phase and the micellar phase and migrated with the EOF in the capillary to achieve separation . Two kinds of surfactant, SDS and SC were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The analytes are distributed between the aqueous phase and the micellar phase and migrated with the EOF in the capillary to achieve separation. 23,24 Two kinds of surfactant, SDS and SC were investigated. SDS was ineffective for the separation of hirsutine and hirsuteine.…”
Section: Concentration Of Scmentioning
confidence: 99%